Regional inflation in a currency union: fiscal policy vs. fundamentals - Margarida Duarte; Alexander L. Wolman (European Central Bank (ECB), 2002)
We develop a general equilibrium model of a two-region currency union. There are two types of goods: non-traded goods, and traded goods for which markets are segmented. Monetary policy is set by a central monetary authority and is non-neutral due to nominal price rigidities. Fiscal policy is determined at the regional level by each region's government. We find that productivity shock alone generate significant variation in inflation across the two countries. Government spending shocks, in contrast, do not account for a significant portion of inflation variation. Varying relative country sie, we find that smaller countries experience higher variability of their inflation differential in response to shocks to productivity growth. Moreover, we show that regional governments can suppress incipient inflation differential associated with shock to productivityt growth by letting the income tax rate respond negatively to inflation differentials.
Keywords: E31; E32; F41; H63; 330